Charge redistribution enhanced oxygen reduction of carbon-based electrocatalyst - Guo, Yuyu (2023)
The surface charge distribution is regarded as a key factor affecting the electrocatalytic performance. Herein, we report a strategy to regulate the surface charge distribution in carbon-based electrocatalyst to enhance its activity and stability in oxygen reduction reaction (ORR). The sample obtained in a sealed reactor N,S co-doped carbon encapsulate Co9S8 nanoparticles (Co9S8@CNS-S) exhibits excellent ORR performance. X-ray photoelectron spectroscopy, kelvin probe force microscopy and density functional theory simulation were used to investigate the mechanism of performance improvement. The enhanced ORR activity was due to the exposed more positive charge of surface carbon atoms by N, S elements doping synergistic with Co9S8 nanoparticles (NPs). The improved ORR stability was attributed to the carbon layer combination with Co9S8 NPs which greatly suppresses the generation of H2O2, thus avoiding the erosion of H2O2 on carbon layer during electrocatalysis. This work provides a strategy to regulate electrocatalyst surface charge distribution to achieve active and stable ORR electrocatalyst.